Proceedings of the International Conference of Science and Technology for the Internet of Things 2019
DOI: 10.4108/eai.19-10-2018.2282821
|View full text |Cite
|
Sign up to set email alerts
|

Character Development In Virtual Class

Abstract: Teachers in the 21st century are challenged to accelerate the development of technology, information, and communication. Teachers also play an important role in the development of students' character. This article informs the results of research in which character values can be developed in virtual classroom learning. Action Research on students of the FKIP UST PKK study program shows that virtual classroom learning is able to develop character values of discipline, honesty, responsibility, communication, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
3
0
1
Order By: Relevance
“…The results showed that problem-based learning e-learning had an effect on inferential statistics learning outcomes. The findings of this study are in line with previous studies [11,12].…”
Section: Resultssupporting
confidence: 94%
“…The results showed that problem-based learning e-learning had an effect on inferential statistics learning outcomes. The findings of this study are in line with previous studies [11,12].…”
Section: Resultssupporting
confidence: 94%
“…The development of the media is one source of learning in blended learning. This helps lecturers improve collaborative learning [14], [20].…”
Section: Subtitles and Materials About England Laminationmentioning
confidence: 99%
“…First, character development is carried out by schools through the learning process by implementing interactive classroom activities [11]. This includes the development of students' character in virtual classroom activities, which develop discipline, honesty, responsibility, communication, and collaboration [12]. Second, student character development is accomplished by creating a conducive school environment.…”
Section: Introductionmentioning
confidence: 99%